Strand 2: Building a Virtual Workshop: Collaboration based on Internet Technology - Mikalsen, Arne B. (Proceedings of the International Conference on Networked Learning, 1998)
Learning has always been expressed by means of learning goals. Such learning goals could typically be integration of theory and practise, learn to underlie arguments and collaboration (project work). Traditionally, university students have organised themselves in colloquial groups, to achieve richer learning. Discussing the curriculum with other students have always been considered excellent pedagogy. In recent years, more students are studying parttime, often full- or part-time employed. In this lifelong learning (LLL) field, distance learning become important and very effective. The students are not able (or at least unwilling) to leave their work for several days, attending a course. They want to stay at work, or with their families, studying. This implies that they are often left on their own, with no other students attending the course to discuss with face to face. If we can scare that collaboration is good pedagogy, how shall we overcome the lack of presence of other students? This paper will discuss collaboration in open and distance learning, more specifically Computer Supported Co-operative Learning (CSCL). McConnell (1) defines CSCL as (p. 8): "No matter how distant each member is, they all have a need to work together on some aspects of their learning, and do this through the use of computers. I call this form of co-operative learning computer supported co-operative learning (CSCL)."